THE CONCEPT OF “HATRED” IN THE UKRAINIANS LANGUAGE PICTURE OF THE WORLD DURING THE GREAT WAR 2022–2023 - Khrystianinova, Raisa (Linguistic Bulletin (Movoznavchyi Visnyk), 2023)
Introduction. In the context of the full-scale Russian-Ukrainian war of 2022–2023, in scientific works on philosophy and psychology a shift in the nature of hatred was ascertained and specified as retaliatory hatred. The new interpretation of the feeling of hatred requires as well a study of changes in the interpretation of the concept “hatred” – a mental unit that captures the Ukrainians perception of this feeling, that determines the relevance of the proposed intelligence. Purpose. To identify and justify changes in the concept interpretation of “hatred” in the great war of 2022–2023 realities based on the analysis of the representation means of this concept in Ukrainians language picture of the world. Methods: analysis of philosophical, psychological and linguistic scientific works, which consider the problem – to outline the theoretical background of the study; structural method, in particular its methodology of component analysis – for determining the seme compound of the lexeme “hatred” and the lexemes of enemies’ names; contextual analysis – to reveal the connotation of a word in context; interpretation method – for content clarification of the lexemes of names; descriptive method – for systematization and classification of the studied linguistic material. Results. The analysis of the enemy’s names used by the Ukrainians gives grounds to single out a complex of features of the Russian occupiers: unworthy titles of a person because of their ugly deeds, disgusting outwardly and inwardly, zombified by propaganda, unable to assess the real state of affairs independently. All of this gives rise to a just hatred toward the enemy and sets a productive motivation for protection aimed to safe yourself, own country, restoring social order, maintaining the vertical of values, which is the core of each culture and civilization. Originality. The concept of “hatred” in the Ukrainians language picture of the world during the fullscale war of 2022–2023 has undergone significant changes and can be specified as “retaliatory hatred”. Conclusion. The main characteristics of the concept of “retaliatory hatred” are: 1) high intensity emotions; 2) originated by a feeling of disgust for a vile enemy, who unworthy title of a person; 3) foresee the destruction of the enemy, as he is a threat to the values of coexistence created by humanity; 4) is aimed to defend the democratic ideals of a civilized society, therefore, it has a constructive character.